The Forest: An African Traditional Definition - Inyang, Ekpe (Book collections on Project MUSE., 2015)
The Forest: An African Traditional Definition is aimed at providing the conservationist with some basic ideas as to which cultural areas to explore (using a few African cultures-from some ecologically and culturally rich forest zones of Cameroon that has earned the description of Africa in miniature due to its diversity and representativeness of ecological and cultural landscape that reflect the continent-for illustration) in order to direct him or her to the appropriate beliefs and customs that could be exploited in favour of conservation. There is no overemphasising that most, if not all, African cultures have at least some rudimentary aspects of conservation in the modern sense. These aspects constitute the strong colours that could be used to create an indelible picture of the importance of conservation on the continent.